PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH BANK BNI JALAN JENDERAL SUDIRMAN SERTA DAMPAKNYA TERHADAP LOYALITAS NASABAH - Dwi Angkoso, Yudhi (Aksara Public, 2019)
This research has aim to know the influence of service quality on customer’s satisfaction, the influence of customer’s satisfaction on customer’s loyalty, and the influence of service quality on customer’s loyalty. The data conducted by distributing questionnaire to 100 of respondents of BNI Jalan Sudirman branch. This questionnaire composed of 21 items with 5 options of scale and was analyzed by path analysis. The result of this research which showed service quality influences customer’s satisfaction significantly with total contribution as 52,7%, customer’s satisfaction influences customer’s loyalty significantly with total contribution as 14,1% and service quality influences customer’s loyalty significantly with total contribution as 12,8%. Another result the direct determination coefficient of service quality on customer loyalty is higher than indirect determination coefficient of service quality on customer’s loyalty through customer’s satisfaction. Direct determination indicated by score of 46,3% and indirect determination indicated by score of 12,8%. It was concluded that customer’s satisfaction as intervening variable which bridges service quality and customer’s loyalty